The impact of learning in a diversified environment: social and cognitive development of international students for global mind-set. Issue 5 (15th June 2021) - Khalid, Muhammad Saifullah; Zhanyong, Qi; Bibi, Jannat
Abstract : Purpose: This study aims to assess the socio-cognitive transformation and subject knowledge development of international students studying in China's universities with diverse learning environment. Design/methodology/approach: The data was collected through on-line survey and quantitative approach was adopted on a Likert scale to assess students' cognitive and social development as a responsible mind-set, ethical awareness, understanding cultural diversity and subject knowledge development. The assessment scale consisted of 25 statements to cover the foundational indicators that represent socio-cognitive transformation. The questionnaire was pilot tested for internal consistency by calculating Cronbach's alpha. Furthermore, exploratory factor analysis was applied to ensure the traits of the construct intended to measure. A total of 316 participants responded to the survey. With descriptive statistics, X 2 of association and Friedman's two-way analysis of variance by rank was applied to test the hypothesis. Findings: This study argues that diverse learning environment has positive impact on learners' socio-cognitive transformation. It enhances students' capability to understand cultural values to accept diversity and awareness about global community issues and also subject knowledge skill development. Originality/value: In the current century, study abroad programs have increased the mobility of international students, and the role of higher education institutions has become immense, multifaceted and dynamic. Universities are taking a position to play a considerable role in creating learning opportunities for awareness of societal issues and transform social behavior. Studying abroad programs is a growing concept in response to learners' cogitative and socialized transformation. There is an absence of research conducted to explore the impact of a diverse cultural environment on the socio-cognitive transformation of international students. Therefore, the current study focused on exploring the cognitive and societal development of international students studying in China.